A SILAR method for the fabrication of layer-by-layer assembled Cu2O-reduced graphene oxide composite for non-enzymatic detection of hydrogen peroxide. (23rd November 2018) - Kumar, J Sharath; Murmu, Naresh Chandra; Banerjee, Amit; Ganesh, R Sankar; Inokawa, Hiroshi; Kuila, Tapas
Abstract: Hydrogen peroxide (H2 O2 ) is an important synthetic precursor as well as degradation product of many peroxide-based explosives. Herein, a facile method for the synthesis of Cu2 O-reduced graphene oxide (CRGO) composite has been demonstrated which would be used as active electrode material for the detection of H2 O2 . Successive Ionic Layer Adsorption and Reaction (SILAR) mechanism for the synthesis of layer-by-layer (LbL) assembly has been undertaken to yield homogenously anchored Cu2 O NPs over large surface of reduced graphene oxide (RGO). Fourier transform infrared and x-ray photoelectron spectroscopic studies revealed the removal of oxygen functionalities from graphene oxide (GO) and the successful formation of RGO. X-ray diffraction studies confirms the formation of Cu2 O NPs. Microscopic characterization was carried out by field emission scanning electron (FESEM) and transmission electron microscopy (TEM) which revealed the successful decoration of graphene surface homogenously by Cu2 O NPs. The electrochemical characterization was carried out through cyclic voltammetry and chronoamperometry, which suggested the utilization of CRGO composite for the detection of H2 O2 with a sensitivity of 74.99 μ A μ M −1 cm −2 and the LoD of 1.05 nM. The interference test suggested superior selectivity of the composite for H2 O2 against various other analytes.